Ten Research Questions for Improving COPD Care in the Next Decade. (2nd November 2019) - López-Campos, José Luis; Rodríguez, Diego A.; Quintana-Gallego, Esther; Martínez-Llorens, Juana; Carrasco Hernández, Laura; Barreiro, Esther
Abstract: With the 60th anniversary of the CIBA symposium, it is worth evaluating research questions that should be prioritized in the future. Coming research initiatives can be summarized in 10 main areas. (1) From epidemiology the impact of new forms of electronic cigarettes on prevalence and mortality of COPD will be sought. (2) The study of the disease endotypes and its relationship phenotypes will have to be unraveled in the next decade. (3) Diagnosis of COPD faces several challenges opening the possibility of a change in the definition of the disease itself. (4) Patients' classification and risk stratification will need to be clarified and reassessed. (5) The asthma-COPD overlap dilemma will have to be clarified and define whether both conditions represent one only chronic airway disease again. (6) Integrating comorbidities in COPD care will be key in a progressively ageing population to improve clinical care in a chronic care model. (7) Nonpharmacological management have areas for research including pulmonary rehabilitation and vaccines. (8) Improving physical activity should focus research because of the clear prognostic impact. (9). Pharmacological therapies present several challenges including efficacy and safety issues with current medications and the development of biological therapy. (10) The definition, identification, categorization and specific therapy of exacerbations will also be an area of research development. During the next decade, we have a window of opportunity to address these research questions that will put us on the path for precision medicine.